United Republic of Tanzania : Sixth Review Under the Policy Support Instrument and Request for a Six-Month Extension of the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Tanzania's Sixth Review Under the Policy Support Instrument (PSI) and Request for a Six-Month Extension of the PSI. Tanzania's macroeconomic performance has been strong, albeit with a recent deceleration in economic growth. Program performance under the PSI has been broadly satisfactory. Most quantitative targets for December 2016 and March 2017 were met. Although progress in structural reforms identified under the program has been generally slow, the authorities have stepped up efforts to advance them. The IMF staff supports the authorities' request for a 6-month extension of the PSI arrangement and recommends completion of its sixth review.